Phytochemical analysis of three wild edible portuguese fruits that may provide potential health benefits - Albuquerque, Carina (2021)
Portuguese flora is recognized for its high biodiversity. Many underutilized wild fruits have great nutritional and functional potentials, providing chemical compounds with biological properties. In this work, the phytochemical composition and antioxidant activity of three wild edible fruits (Arbutus unedo L., Crataegus monogyna Jacq., and Rosa canina L.), collected in the North of Portugal, were evaluated. Hydroalcoholic extracts were prepared from fresh fruits, and total phenolics, flavonoids and anthocyanins contents were determined. Moreover, two different assays were used to evaluate antioxidant activity: 2,2-diphenyl-1-picrylhydrazyl radical (DPPH• ) inhibition assay and ferric reducing antioxidant power (FRAP). As expected, a wide variability was found in the composition of these three wild Portuguese fruits. Phytochemical screening revealed considerable amounts of total phenolics (65-150 mg gallic acid eq./100 g), total flavonoids (126-180 mg epicatechin eq./100 g) and anthocyanins (1.66-29.6 mg cyanidin-3-glycoside eq./100 g). Extracts of Arbutus unedo L. fruits presented the highest antioxidant activity, followed by Crataegus monogyna Jacq., and Rosa canina L., by this order.